High-performance negative mixing enthalpy rare earth high manganese steel material and preparation method thereof

CN122918449APending Publication Date: 2026-10-16SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611398885.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-10
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0006]基于上述现有技术的不足,本发明的目的在于提供一种高性能负混合焓的稀土高锰钢材料及其制备方法,旨在解决现有高锰钢低强度、高密度和耐蚀性差的问题

Benefits of technology

[0044] (1) This invention provides a Fe a Mn b Al c Cr d Mo e Pb f RE g Si h C i This series of high-performance rare earth high-manganese steel materials with negative mixed enthalpy are composed of iron, manganese, aluminum, chromium, molybdenum, lead, rare earth (cerium and gadolinium), silicon and carbon elements, and are produced by vacuum electric arc melting furnace. The structure of this series of negative mixed enthalpy high-manganese steels is FCC structure, and the alloy density and mechanical properties can be controlled by adjusting the element ratio.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122918449A_ABST
    Figure CN122918449A_ABST
Patent Text Reader

Abstract

The application discloses a high-performance negative mixing enthalpy rare earth high manganese steel material and a preparation method thereof a Mn b Al c Cr d Mo e Pb f RE g Si h C i ; RE is Ce or Gd, a, b, c, d, e, f, g, h and i respectively correspond to the molar percentage of each element, 16%≤b≤20%, 8%≤c≤12%, 7%≤d≤9%, 0<e≤1.8%, 0≤f≤0.1%, 0<g≤0.1%, 1%≤h≤3%, 2%≤i≤5%, and the balance is Fe and inevitable impurities. The application introduces Al and Cr, can form a dense passivation film on the surface of high manganese steel, introduces Mo to improve the stability of the passivation film, introduces Pb to reduce the problem of reducing the prevalence caused by the negative enthalpy element; taking rare earth Ce and Gd as the core regulation component, the microstructure of the alloy can be accurately controlled, and the synergistic effect of low density, high strength, high toughness and corrosion resistance is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of metallic materials technology, and relates to a high-performance rare earth high-manganese steel material with negative mixed enthalpy and its preparation method. Background Technology

[0002] Metallic structural materials serve as the base material for advanced defense weaponry and high-precision equipment. Their superior strength, plasticity, and corrosion resistance determine the sophistication and safety of these devices. Furthermore, reducing material density (increasing specific strength) can significantly reduce weight and improve fuel economy. However, the specific strength, plasticity, and corrosion resistance of materials are mutually restrictive, making it difficult to achieve synergistic improvements. Therefore, developing low-density metallic structural materials that combine high strength, high plasticity, and high corrosion resistance has become a persistent pursuit for researchers.

[0003] High-manganese steel refers to alloy steel with a manganese content of more than 10%. After water quenching, high-manganese steel exhibits a single-phase austenitic structure, displaying excellent tensile toughness, impact toughness, durability, and high-temperature stability, making it one of the most ideal materials in the automotive industry. However, high-manganese steel typically exhibits lower strength (tensile strength in homogenized state ~600 MPa) and higher density (~7.7 g / cm³). 3 It also has poor corrosion resistance.

[0004] The development of high-strength, high-toughness, high-corrosion-resistance, and lightweight steel is a key focus in the field of metallic materials. New rare-earth modified high-manganese steel aligns with the current market demand for the transformation and upgrading of the steel industry. The development of negative mixed-enthalpy rare-earth high-manganese steel, which combines low density, high strength, high toughness, and high corrosion resistance, not only holds promise for addressing the lack of high-performance metallic materials in major national projects such as automobiles, defense weaponry, and deep-earth and deep-sea engineering, but also promotes its practical application in key corrosion-resistant structural components in coal, chemical, industrial production, and national defense, thus playing a significant role in building a modern industrial system.

[0005] In view of this, the present invention is proposed. Summary of the Invention

[0006] Based on the shortcomings of the prior art, the purpose of this invention is to provide a high-performance rare earth high-manganese steel material with negative mixed enthalpy and its preparation method, aiming to solve the problems of low strength, high density and poor corrosion resistance of existing high-manganese steel.

[0007] The present invention adopts the following technical solution:

[0008] A high-performance rare-earth high-manganese steel material with negative mixing enthalpy, wherein the rare-earth high-manganese steel material is Fe a Mn b Al c Cr d Mo e Pbf RE g Si h C i ;in:

[0009] RE is either Ce or Gd;

[0010] a, b, c, d, e, f, g, h, and i correspond to the molar percentages of each element, with 16% ≤ b ≤ 20%, 8% ≤ c ≤ 12%, 7% ≤ d ≤ 9%, 0 < e ≤ 1.8%, 0 ≤ f ≤ 0.1%, 0 < g ≤ 0.1%, 1% ≤ h ≤ 3%, and 2% ≤ i ≤ 5%, with the balance being Fe and unavoidable impurities.

[0011] The rare earth high manganese steel material has a face-centered cubic structure.

[0012] Research has revealed that, in the design of alloy chemical composition, compared with traditional high-manganese steel, on the one hand, the introduction of Al and Cr alloying elements, while significantly increasing the content of Si and C elements, can reduce the density of the alloy. Simultaneously, the introduction of Al and Cr alloying elements can form a dense passivation film on the surface of high-manganese steel, and the introduction of Mo can improve the stability of the passivation film. The introduction of Pb element helps to reduce the volatility reduction caused by negative enthalpy elements through micro-alloying. On the other hand, using rare earth elements Ce and Gd as core control components can precisely control the microstructure of the alloy and improve the comprehensive performance of the material, which is the core of achieving synergistic optimization of multiple material properties.

[0013] In the above technical solution, the purity of the iron, manganese, aluminum, chromium, molybdenum, lead, cerium, gadolinium, silicon and carbon elements in the rare earth high manganese steel material is ≥99.8%.

[0014] In the above technical solutions, rare earth elements cerium (Ce) and gadolinium (Gd) exhibit different atomic bonding characteristics.

[0015] Specifically, in the above technical solution, the rare earth high-manganese steel material,

[0016] The enthalpy of mixing of cerium and gadolinium with iron and manganese are both between -1 and 3 kJ / mol, respectively, indicating weak interactions.

[0017] The enthalpy of mixing between cerium and gadolinium with chromium and molybdenum are both between 10 and 30 kJ / mol, respectively, indicating a significant chemical repulsion effect.

[0018] The enthalpy of mixing cerium and gadolinium with aluminum, lead, silicon and carbon are all between -120 and -30 kJ / mol.

[0019] The mixed enthalpy of lead with iron, manganese, aluminum, chromium and molybdenum is between 10 and 50 kJ / mol, which helps to reduce the problem of reduced mobility caused by negative enthalpy elements.

[0020] In detail, in the above technical solution, the mixing enthalpy values ​​of the binary system related to cerium and gadolinium are as follows: ΔH mix (Ce-Fe) = 3 kJ / mol, ΔH mix (Ce-Mn) = 1 kJ / mol, ΔH mix (Ce-Al) = -38 kJ / mol, ΔH mix (Ce-Cr) = 15 kJ / mol, ΔH mix (Ce-Si) = -73 kJ / mol, ΔH mix (Ce-C) = -116 kJ / mol, ΔH mix (Gd-Fe) = -1 kJ / mol, ΔH mix (Gd-Mn) = -1 kJ / mol, ΔH mix (Gd-Al) = -39 kJ / mol, ΔH mix (Gd-Cr) = 11 kJ / mol, ΔH mix (Gd-Si) = -73 kJ / mol, ΔH mix (Gd-C) = -117 kJ / mol.

[0021] Specifically, the addition of rare earth elements cerium and gadolinium is expected to significantly expand the difference in chemical affinity between atoms, thereby forming localized heterogeneous structures of negative mixed enthalpy chemical affinity clusters in the austenitic structure, achieving a synergistic effect of high tensile strength and large tensile plasticity; the strong and stable atomic bonds (ΔH) formed between rare earth elements and carbon mix (Cr-C) = -61 kJ / mol, far exceeding the enthalpy of mixing of rare earth elements and carbon. Furthermore, thermodynamic calculations using ThermoCalc software confirmed that this inhibits chromium carbide precipitation, increasing the alloy's corrosion resistance. Secondly, the introduction of strong local chemical interactions within the alloy slows down the dissolution rate of the metal, further enhancing corrosion resistance. Ultimately, this rare earth high-manganese steel with negative enthalpy of mixing achieves a synergistic effect of low density, high strength, high toughness, and corrosion resistance.

[0022] Specifically, in the above technical solution, the rare earth high-manganese steel material is Fe. 55.92 Mn 18 Al 11 Cr8Mo1Ce 0.08 Si2C4, Fe 56.48 Mn 18 Al11 Cr8Mo 0.50 Ce 0.02 Si2C4, Fe 56.73 Mn 18 Al 11 Cr8Mo 0.25 Ce 0.02 Si2C4, Fe 55.98 Mn 18 Al 11 Cr8Mo1Gd 0.02 Si2C4, Fe 55.96 Mn 18 Al 11 Cr8Mo1Gd 0.04 Si2C4, Fe 55.92 Mn 18 Al 11 Cr8Mo1Gd 0.08 Si2C4, Fe 59.22 Mn18Al9Cr8Mo 0.7 Ce 0.08 Si2C3, Fe 59.18 Mn 18 Al9Cr8Mo 0.7 Ce 0.08 Pb 0.04 Si2C3, Fe 59.68 Mn 18 Al9Cr8Mo 0.7 Ce 0.08 Pb 0.04 Si 1.5 One of C3.

[0023] In the above technical solution, the mixed enthalpy of the rare earth high manganese steel material is between -16 and -10 kJ / mol.

[0024] In detail, in the above technical solution, the Fe 55.92 Mn 18 Al 11 Cr8Mo1Ce 0.08 Si2C4, Fe 56.48 Mn 18 Al 11 Cr8Mo 0.50 Ce 0.02 Si2C4, Fe 56.73 Mn 18 Al 11 Cr8Mo 0.25 Ce 0.02 Si2C4, Fe 55.98 Mn 18 Al 11Cr8Mo1Gd 0.02 Si2C4, Fe 55.96 Mn 18 Al 11 Cr8Mo1Gd 0.04 Si2C4, Fe 55.92 Mn 18 Al 11 Cr8Mo1Gd 0.08 Si2C4, Fe 59.22 Mn 18 Al9Cr8Mo 0.7 Ce 0.0 8Si2C3, Fe 59.18 Mn 18 Al9Cr8Mo 0.7 Ce 0.08 Pb 0.04 Si2C3, Fe 59.68 Mn 18 Al9Cr8Mo 0.7 Ce 0.08 Pb 0.04 Si 1.5 The mixed enthalpy values ​​of C3 rare earth high manganese steel materials are -14.96 kJ / mol, -15.16 kJ / mol, -15.23 kJ / mol, -14.94 kJ / mol, -14.95 kJ / mol, -14.97 kJ / mol, -12.52 kJ / mol, -12.46 kJ / mol and -11.87 kJ / mol, respectively.

[0025] In another aspect, the present invention also provides a method for preparing the above-mentioned high-performance rare-earth high-manganese steel material with negative enthalpy of mixing.

[0026] The rare earth high-manganese steel material is Fe. a Mn b Al c Cr d Mo e Pb f RE g Si h C i ;

[0027] Where: RE is Ce or Gd;

[0028] a, b, c, d, e, f, g, h, and i correspond to the molar percentages of each element, with 16% ≤ b ≤ 20%, 8% ≤ c ≤ 12%, 7% ≤ d ≤ 9%, 0 < e ≤ 1.8%, 0 ≤ f ≤ 0.1%, 0 < g ≤ 0.1%, 1% ≤ h ≤ 3%, and 2% ≤ i ≤ 5%, with the balance being Fe and unavoidable impurities.

[0029] The rare earth high manganese steel material has a face-centered cubic structure.

[0030] The preparation method of the rare earth high-manganese steel material includes the following steps:

[0031] According to the composition and molar percentage of the rare earth high manganese steel material, calculate and weigh each metal raw material, and put each metal raw material into the water-cooled metal crucible in order of melting point from low to high. The metal raw material with the lowest melting point is placed at the bottom and the metal raw material with the highest melting point is placed on the surface. Sponge titanium is placed in the middle copper mold. Arc melting is carried out in an oxygen-free environment until it is fully mixed to obtain the rare earth high manganese steel material.

[0032] In the above technical solution, the oxygen-free environment is achieved through a process of vacuuming, filling with argon gas, and melting sponge titanium to absorb oxygen.

[0033] Furthermore, in a preferred embodiment of the present invention, the process of vacuuming, argon filling, and oxygen absorption during the melting of sponge titanium specifically comprises:

[0034] Use a mechanical pump to evacuate to a vacuum level of less than 5. Pa, then a molecular pump was used to evacuate the vacuum to a level less than 7 × 10⁻⁶. -4 Pa, then 99.99% pure argon gas is introduced until 0.05 ppm is reached. MPa, and finally the sponge titanium is melted twice by arc ignition (each time the sponge titanium is melted by arc ignition, that is, the sponge titanium is heated at high temperature by electric arc and melts into liquid state visible to the naked eye. This melting process absorbs oxygen) to absorb residual oxygen.

[0035] In the above technical solution, the number of times the metal raw material is ignited and melted is greater than 4. After each ignition and melting, the alloy in the crucible is turned over before the next ignition and melting. Before the next ignition and melting of the alloy, the sponge titanium is melted and oxygen absorbed twice.

[0036] In the above technical solution, the melting time for each arc ignition melting is 1.0-2.0 min, and in addition to the first and last arc ignition melting, the arc ignition melting of the metal raw material also includes magnetic stirring of the melt.

[0037] Specifically, in the above technical solution, the melting voltage and melting current of the arc-ignition melting are 10-15 V and 320-450 A, respectively.

[0038] In one specific embodiment of the present invention, the preparation method of the high-performance negative enthalpy rare earth high-manganese steel material specifically includes the following steps:

[0039] S1. Place the high-purity raw material particles (Fe, Mn, Al, Cr, Mo, Pb, Ce, Gd, Si and C) in an ultrasonic cleaner and clean them twice. Then, after accurately calculating their molar ratio, weigh and mix them. Place them in a water-cooled metal crucible in order of melting point from low to high, with the element with the lowest melting point at the bottom and the element with the highest melting point at the top. At the same time, place sponge titanium at the middle copper mold position.

[0040] S2. Close the electric arc melting furnace door, turn on the circulating water, turn on the mechanical pump, and begin vacuuming. When the vacuum level is below 5 Pa, turn on the molecular pump for further vacuuming. When the vacuum level is below 7.0 × 10⁻⁶ Pa... -4 At Pa, high-purity argon gas (purity of 99.99% and pressure of approximately 0.05 MPa) is introduced as a protective gas. Arc ignition is performed in the high-purity argon atmosphere to melt the sponge titanium twice and absorb residual oxygen in the furnace.

[0041] S3. First, high-current melting (melting voltage 10-15 V, melting current 320-450 A) is used to melt and mix all metal particles evenly. After the alloy button is cast and cooled, it is flipped by a robotic arm and melted in the same way. Magnetic stirring is turned on during each subsequent melting process. After each melting, the alloy button is flipped 180 degrees. A total of 5 melting processes are carried out to make the alloy composition more uniform. Magnetic stirring is turned off during the last melting process to make it a smooth ingot, which is then suction-cast.

[0042] S4. After the alloy button ingot has completely cooled, open the furnace door and take out the sample.

[0043] Compared with the prior art, the beneficial effects of the present invention are:

[0044] (1) This invention provides a Fe a Mn b Al c Cr d Mo e Pb f RE g Si h C i This series of high-performance rare earth high-manganese steel materials with negative mixed enthalpy are composed of iron, manganese, aluminum, chromium, molybdenum, lead, rare earth (cerium and gadolinium), silicon and carbon elements, and are produced by vacuum electric arc melting furnace. The structure of this series of negative mixed enthalpy high-manganese steels is FCC structure, and the alloy density and mechanical properties can be controlled by adjusting the element ratio.

[0045] (2) The Fe provided by the present invention a Mn b Al c Cr d Moe Pb f RE g Si h C i A series of high-performance rare-earth high-manganese steel materials with negative mixing enthalpy are characterized by low density, among which: Fe 55.92 Mn 18 Al 11 Cr8Mo1Ce 0.08 The density of Si2C4 is 6.68 g / cm³. 3 Fe 56.48 Mn 18 Al 11 Cr8Mo 0.50 Ce 0.02 The density of Si2C4 is 6.67 g / cm³. 3 Fe 56.73 Mn 18 Al 11 Cr8Mo 0.25 Ce 0.02 The density of Si2C4 is 6.66 g / cm³. 3 Fe 55.98 Mn 18 Al 11 Cr8Mo1Gd 0.02 The density of Si2C4 is 6.67 g / cm³. 3 Fe 55.96 Mn 18 Al 11 Cr8Mo1Gd 0.04 The density of Si2C4 is 6.68 g / cm³. 3 Fe 55.92 Mn 18 Al 11 Cr8Mo1Gd 0.08 The density of Si2C4 is 6.68 g / cm³. 3 Fe 59.22 Mn 18 Al9Cr8Mo 0.7 Ce 0.08 The density of Si2C3 is 6.82 g / cm³. 3 Fe 59.18 Mn 18 Al9Cr8Mo 0.7 Ce 0.08 Pb 0.04 The density of Si2C3 is 6.84 g / cm³. 3 Fe 59.68 Mn 18 Al9Cr8Mo 0.7 Ce 0.08 Pb 0.04 Si1.5 The density of C3 is 6.88 g / cm³. 3 .

[0046] (3) The Fe provided by the present invention a Mn b Al c Cr d Mo e Pb f RE g Si h C i A series of high-performance rare-earth high-manganese steel materials with negative mixing enthalpy possess both high strength and high plasticity in terms of mechanical properties, among which: Fe 55.92 Mn 18 Al 11 Cr8Mo1Ce 0.08 The room temperature tensile yield strength of Si2C4 is 483 MPa, the breaking strength is 890 MPa, and the uniform elongation is 45.0%; Fe 56.48 Mn 18 Al 11 Cr8Mo 0.50 Ce 0.02 The room temperature tensile yield strength of Si2C4 is 357 MPa, the breaking strength is 758 MPa, and the uniform elongation is 63.1%; Fe 56.73 Mn 18 Al 11 Cr8Mo 0.25 Ce 0.02 The room temperature tensile yield strength of Si₂C₄ is 380 MPa, the breaking strength is 830 MPa, and the uniform elongation is 68.1%; Fe 55.98 Mn 18 Al 11 Cr8Mo1Gd 0.02 The room temperature tensile yield strength of Si₂C₄ is 400 MPa, the breaking strength is 847 MPa, and the uniform elongation is 63.1%; Fe 55.96 Mn 18 Al 11 Cr8Mo1Gd 0.04 The room temperature tensile yield strength of Si2C4 is 407 MPa, the breaking strength is 857 MPa, and the uniform elongation is 55.9%; Fe 55.92 Mn 18 Al 11 Cr8Mo1Gd 0.08 The room temperature tensile yield strength of Si2C4 is 395 MPa, the breaking strength is 644 MPa, and the uniform elongation is 22.3%; Fe 59.22 Mn 18 Al9Cr8Mo 0.7 Ce0.08 The room temperature tensile yield strength of Si2C3 is 477 MPa, the breaking strength is 920 MPa, and the uniform elongation is 42.3%; Fe 59.18 Mn 18 Al9Cr8Mo 0.7 Ce 0.08 Pb 0.04 The room temperature tensile yield strength of Si2C3 is 509 MPa, the breaking strength is 963 MPa, and the uniform elongation is 44.6%; Fe 59.68 Mn 18 Al9Cr8Mo 0.7 Ce 0.08 Pb 0.04 Si 1.5 The C3 has a room temperature tensile yield strength of 460 MPa, a breaking strength of 910 MPa, and a uniform elongation of 48.2%.

[0047] (4) The Fe provided by the present invention a Mn b Al c Cr d Mo e Pb f RE g Si h C i A series of high-performance rare-earth high-manganese steel materials with negative mixing enthalpy exhibit good corrosion resistance, among which: Fe 55.92 Mn 18 Al 11 Cr8Mo1Ce 0.08 The corrosion potential of Si2C4 is -0.17V, and the pitting potential is 0.10V; Fe 56.48 Mn 18 Al 11 Cr8Mo 0.50 Ce 0.02 The corrosion potential of Si2C4 is -0.26V, and the pitting potential is -0.07V; Fe 56.73 Mn 18 Al 11 Cr8Mo 0.25 Ce 0.02 The corrosion potential of Si2C4 is -0.21V, and the pitting potential is -0.04V; Fe 55.98 Mn 18 Al 11 Cr8Mo1Gd 0.02 The corrosion potential of Si2C4 is -0.19V, and the pitting potential is 0.15V; Fe 55.96 Mn 18 Al 11 Cr8Mo1Gd 0.04The corrosion potential of Si2C4 is -0.18V, and the pitting potential is 0.08V; Fe 55.92 Mn 18 Al 11 Cr8Mo1Gd 0.08 The corrosion potential of Si2C4 is -0.16V, and the pitting potential is -0.01V; Fe 59.22 Mn 18 Al9Cr8Mo 0.7 Ce 0.08 The corrosion potential of Si2C3 is -0.24V, and the pitting potential is 0.01V; Fe 59.18 Mn 18 Al9Cr8Mo 0.7 Ce 0.08 Pb 0.04 The corrosion potential of Si2C3 is -0.17V, and the pitting potential is -0.04V; Fe 59.68 Mn 18 Al9Cr8Mo 0.7 Ce 0.08 Pb 0.04 Si 1.5 The corrosion potential of C3 is -0.19V, and the pitting potential is -0.08V. Attached Figure Description

[0048] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0049] Figure 1 The Fe prepared in Examples 1-9 of this invention a Mn b Al c Cr d Mo e Pb f RE g Si h C i X-ray diffraction patterns of a series of high-performance rare-earth high-manganese steel materials with negative mixed enthalpy and high-manganese steel materials prepared in Comparative Examples 1-2;

[0050] Figure 2 The Fe prepared in Examples 1-9 of this invention a Mn b Al c Cr d Mo e Pb f REg Si h C i Room temperature tensile stress-strain curves of a series of high-performance rare-earth high-manganese steel materials with negative enthalpy of mixing and high-manganese steel materials prepared in Comparative Examples 1-2.

[0051] Figure 3 The Fe prepared in Examples 1-3 of this invention a Mn b Al c Cr d Mo e Pb f RE g Si h C i Room temperature potentiodynamic polarization curves of 3.5 wt.% NaCl in a series of high-performance rare-earth high-manganese steel materials with negative mixed enthalpy;

[0052] Figure 4 The Fe prepared in Examples 4-6 of this invention a Mn b Al c Cr d Mo e Pb f RE g Si h C i Room temperature potentiodynamic polarization curves of 3.5 wt.% NaCl in a series of high-performance rare-earth high-manganese steel materials with negative mixed enthalpy;

[0053] Figure 5 The Fe prepared in Examples 7-9 of this invention a Mn b Al c Cr d Mo e Pb f RE g Si h C i Room temperature potentiodynamic polarization curves of 3.5 wt.% NaCl in a series of high-performance rare-earth high-manganese steel materials with negative mixed enthalpy;

[0054] Figure 6 The table shows the room temperature potentiodynamic polarization curves of the high-manganese steel materials prepared in Comparative Examples 1-2 of this invention with 3.5 wt.% NaCl. Detailed Implementation

[0055] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments.

[0056] It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention.

[0057] In the embodiments, unless otherwise specified, all methods used are conventional methods in the art.

[0058] The terms “comprising,” “including,” or any other variations thereof, as used herein, are intended to cover non-exclusive inclusion. For example, a composition, step, method, article, or apparatus that includes the listed elements is not necessarily limited to those elements, but may include other elements not expressly listed or elements inherent to such composition, step, method, article, or apparatus.

[0059] Furthermore, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0060] This invention provides a Fe a Mn b Al c Cr d Mo e Pb f RE g Si h C i A series of high-performance rare-earth high-manganese steel materials with negative mixed enthalpy and their preparation methods are disclosed, wherein: RE is Ce or Gd; a, b, c, d, e, f, g, h and i correspond to the molar percentages of each element, 16%≤b≤20%, 8%≤c≤12%, 7%≤d≤9%, 0<e≤1.8%, 0≤f≤0.1%, 0<g≤0.1%, 1%≤h≤3%, 2%≤i≤5%, and the balance is Fe and unavoidable impurities.

[0061] Fe provided in the embodiments of the present invention a Mn b Al c Cr d Mo e Pb f RE g Si h C i A series of high-performance rare-earth high-manganese steel materials with negative mixing enthalpy possess a face-centered cubic (FCC) structure. By adjusting the proportions of different metal elements, the microstructure and mechanical properties of the alloy can be controlled, particularly the Fe content. a Mn b Al c Cr d Mo e Pb f RE g Si h Ci The mixed enthalpy value of a series of rare earth high manganese steel materials enables them to combine low density, high strength, high toughness and corrosion resistance, and has great application potential in major fields such as aerospace, marine ships and national defense.

[0062] Rare earth elements, as excellent modifying elements, possess multiple mechanisms for purifying molten steel, refining microstructure, and thermodynamic regulation that are not found in conventional alloys. This is beneficial for breaking through the performance limits of traditional high-manganese steel and achieving synergistic improvements in multiple properties. The specific mechanisms of action encompass multiple dimensions: macro-metallurgy, microstructure, and thermodynamics. At the metallurgical level, rare earth elements can effectively purify molten steel, eliminating harmful impurities through deoxidation and desulfurization reactions. Simultaneously, they can regulate the morphology, size, quantity, and distribution of inclusions, modifying elongated and blocky harmful inclusions into fine, dispersed spherical inclusions, significantly reducing internal defects and pitting corrosion sensitivity. At the microstructure regulation level, rare earth elements can refine grains and inhibit crystal growth. The precipitation and growth of coarse and network carbides improve the uniformity of the alloy structure and eliminate matrix defects. At the thermodynamic level, rare earth elements possess unique differential mixing enthalpy characteristics, which can precisely adjust the differences in chemical affinity between different elements in the system at the atomic scale, inducing the formation of nanoscale cluster heterogeneous structures in the matrix, thereby simultaneously achieving strength improvement, density reduction, and enhanced corrosion resistance from a microscopic perspective. At the mechanical property level, the multiple modification effects of rare earth elements can significantly optimize the comprehensive mechanical properties of high manganese steel, with particularly outstanding effects on improving yield strength and low-temperature impact toughness. It can effectively improve the stress concentration phenomenon in the matrix and greatly enhance the material's resistance to fatigue failure.

[0063] Compared to traditional high-manganese alloys, the embodiments of this invention, by adding rare earth elements cerium and gadolinium, are expected to significantly expand the difference in chemical affinity between atoms, thereby forming a localized heterostructure of negative mixed enthalpy chemical affinity clusters in the austenitic structure, achieving a synergistic effect of high tensile strength and large tensile plasticity; the strong and stable atomic bonds formed between rare earth elements and carbon can inhibit the precipitation of chromium carbide, while introducing local strong chemical interactions in the alloy, thereby slowing down the dissolution rate of the metal material and increasing the corrosion resistance of the alloy.

[0064] Specifically, the mixing enthalpy values ​​of the binary system related to cerium (Ce) and gadolinium (Gd) are as follows: ΔH mix (Ce-Fe) = 3 kJ / mol, ΔH mix (Ce-Mn) = 1 kJ / mol, ΔH mix (Ce-Al) = -38 kJ / mol, ΔH mix (Ce-Cr) = 15kJ / mol, ΔH mix (Ce-Si) = -73 kJ / mol, ΔH mix (Ce-C) = -116 kJ / mol, ΔHmix (Gd-Fe) = -1kJ / mol, ΔH mix (Gd-Mn) = -1 kJ / mol, ΔH mix (Gd-Al) = -39 kJ / mol, ΔH mix (Gd-Cr) = 11kJ / mol, ΔH mix (Gd-Si) = -73 kJ / mol, ΔH mix (Gd-C) = -117 kJ / mol.

[0065] Specifically, Fe in the embodiments of the present invention a Mn b Al c Cr d Mo e Pb f RE g Si h C i The mixed enthalpy values ​​of the series of rare earth high manganese steel materials are all between -16 and -10 kJ / mol.

[0066] The embodiments of the present invention also provide Fe a Mn b Al c Cr d Mo e Pb f RE g Si h C i The preparation methods for a series of rare earth high manganese steel materials specifically include:

[0067] Weigh each metal raw material according to the composition and molar percentage of the rare earth high manganese steel material, and place each metal raw material in a water-cooled metal crucible in order of melting point from low to high. Place the metal raw material with the lowest melting point at the bottom and the metal raw material with the highest melting point on the surface (this allows the low melting point raw material to melt first, forming a liquid molten pool as a heat conduction medium, accelerating the melting rate of the high melting point raw material, which can shorten the total melting time; at the same time, it can also avoid the high melting point raw material directly contacting the high temperature arc, causing instantaneous thermal stress, thereby reducing the risk of thermal fatigue cracks in the inner wall of the container). Place sponge titanium in the middle copper mold, and melt it in an oxygen-free environment until it is fully mixed to obtain the rare earth high manganese steel material.

[0068] In detail, the aforementioned oxygen-free environment is achieved through a process of vacuuming, purging with argon gas, and melting sponge titanium to absorb oxygen. Specifically, the process involves using a mechanical pump to evacuate the vacuum to a level less than 5. Pa, then a molecular pump was used to evacuate to a vacuum level less than 7.0 × 10⁻⁶.-4 Pa, then 99.99% pure argon gas is introduced until 0.05 ppm is reached. MPa, and finally arc-ignition melting of sponge titanium twice to absorb residual oxygen.

[0069] In detail, the above-mentioned metal raw materials are ignited and melted more than 4 times. After each ignition and melting, the alloy in the crucible is turned over before the next ignition and melting. Before the next ignition and melting of the alloy, the sponge titanium is melted and oxygen absorbed twice.

[0070] In detail, the melting voltage and melting current for the above-mentioned arc-ignition melting are 10-15 V and 320-450 A, respectively.

[0071] In some embodiments, the current used for arc ignition melting is 320-450 A, for example, it can be 320 A, 330 A, 340 A, 3600 A, 380 A, 4000 A, 410 A, 420 A, 430 A, 440 A or 450 A, etc.

[0072] In some embodiments, the number of arc-ignition melting operations is greater than 4 (e.g., 5, 6, 7, or 8 times), and the time for each arc-ignition melting operation is independently 1-2 minutes (e.g., 1 minute, 1.1 minute, 1.2 minute, 1.3 minute, 1.4 minute, 1.5 minute, 1.6 minute, 1.7 minute, 1.8 minute, 1.9 minute, or 2 minutes). After each arc-ignition melting operation, the alloy in the container is flipped (i.e., rotated 180 degrees) before the next arc-ignition melting operation is performed. The flipping operation can force the melt to flow, promote diffusion homogenization, and help eliminate compositional segregation.

[0073] In some implementations, in addition to the initial and final arc-ignition melting, the melt is stirred (e.g., magnetically stirred) during the arc-ignition melting process. This allows the raw materials to be mixed more thoroughly and evenly, resulting in a more uniform alloy composition.

[0074] In some embodiments, the raw materials are placed into the container in order of increasing melting point, and sponge titanium is added during the process of adding the raw materials; the oxygen-free environment is achieved by vacuuming, filling with argon gas, and absorbing oxygen by melting sponge titanium.

[0075] In some embodiments, the processes of vacuuming, argon filling, and oxygen absorption during the melting of sponge titanium specifically include:

[0076] Vacuum up to 7×10 -4Pa, then 99.99% pure argon gas is introduced to 0.04-0.05 MPa, and the sponge titanium is melted twice by arc ignition to absorb residual oxygen. Finally, a vacuum is drawn to 7×10 Pa. -4 Pa.

[0077] The present invention will be further described below through specific embodiments.

[0078] Example 1

[0079] This embodiment provides a high-performance rare-earth high-manganese steel material with negative enthalpy of mixing, comprising the following molar percentage components: Fe 55.92%, Mn 18%, Al 11%, Cr 8%, Mo 1%, Ce 0.08%, Si 2%, and C 4%, which can be denoted as Fe 55.92 Mn18Al 11 Cr8Mo1Ce 0.08 Si2C4 has a mixing enthalpy of -14.96 kJ / mol.

[0080] The preparation method of the negative enthalpy high-manganese stainless steel material includes the following steps:

[0081] (1) Place the high-purity raw material particles of Fe, Mn, Al, Cr, Mo, Ce, Si and C (all with a purity greater than 99.9%) in an ultrasonic cleaner and clean them twice. Then, according to the molar percentage of each component in Example 1, weigh the high-purity raw material particles of Fe, Mn, Al, Cr, Mo, Ce, Si and C and place them in a water-cooled metal crucible in order of melting point from low to high. Place the raw material particles with the lowest melting point on the top layer and the raw material particles with the highest melting point on the surface layer. Place sponge titanium in the middle copper mold.

[0082] (2) Close the furnace door of the electric arc melting furnace, turn on the circulating water, turn on the mechanical pump, and perform vacuuming. When the vacuum degree is less than 5 Pa, turn on the molecular pump to further vacuum. When the vacuum degree reaches 7.0 × 10 Pa... -4 At Pa, 99.99% pure argon gas (as a protective gas) is introduced to 0.05 MPa, and sponge titanium is arc-melted twice in a high-purity argon atmosphere to absorb residual oxygen;

[0083] (3) Use a large current to perform arc ignition melting of the raw materials (melting voltage 12 V, melting current 400 A, melting time 2 min) to melt and mix all the metal particles evenly. After the alloy button is cast and cooled, it is flipped by a robot and the same method (melting voltage 12 V, melting current 400 A, melting time 2 min) is used to perform the second, third, fourth and fifth arc ignition melting. Magnetic stirring is turned on during each melting process after the second melting. After each melting, the alloy button needs to be flipped 180 degrees. A total of 5 meltings are performed to make the alloy composition more uniform. Magnetic stirring is turned off during the last melting to make it into a smooth ingot and then cast by suction.

[0084] (4) After the alloy button ingot has completely cooled, open the furnace door and take out the sample.

[0085] Example 2

[0086] This embodiment provides a high-performance rare-earth high-manganese steel material with negative enthalpy of mixing, comprising the following molar percentage components: Fe 56.48%, Mn 18%, Al 11%, Cr 8%, Mo 0.5%, Ce 0.02%, Si 2%, and C 4%, which can be denoted as Fe 56.48 Mn 18 Al 11 Cr8Mo 0.50 Ce 0.02 Si2C4 has a mixing enthalpy of -15.16 kJ / mol.

[0087] The preparation method of the negative enthalpy high-manganese stainless steel material includes the following steps:

[0088] (1) Place the high-purity raw material particles of Fe, Mn, Al, Cr, Mo, Ce, Si and C (all with a purity greater than 99.9%) in an ultrasonic cleaner and clean them twice. Then, according to the molar percentage of each component in Example 2, weigh the high-purity raw material particles of Fe, Mn, Al, Cr, Mo, Ce, Si and C and place them in a water-cooled metal crucible in order of melting point from low to high. Place the raw material particles with the lowest melting point on the top layer and the raw material particles with the highest melting point on the surface layer. Place sponge titanium in the middle copper mold.

[0089] (2) Close the furnace door of the electric arc melting furnace, turn on the circulating water, turn on the mechanical pump, and perform vacuuming. When the vacuum degree is less than 5 Pa, turn on the molecular pump to further vacuum. When the vacuum degree reaches 7.0 × 10 Pa... -4 At Pa, 99.99% pure argon gas (as a protective gas) is introduced to 0.05 MPa, and sponge titanium is arc-melted twice in a high-purity argon atmosphere to absorb residual oxygen;

[0090] (3) Use a large current to perform arc ignition melting of the raw materials (melting voltage 12 V, melting current 420 A, melting time 2 min) to melt and mix all the metal particles evenly. After the alloy button is cast and cooled, it is flipped by a robot and the same method (melting voltage 12 V, melting current 420 A, melting time 2 min) is used to perform the second, third, fourth and fifth arc ignition melting. Magnetic stirring is turned on during each melting process after the second melting. After each melting, the alloy button needs to be flipped 180 degrees. A total of 5 meltings are performed to make the alloy composition more uniform. Magnetic stirring is turned off during the last melting to make it a smooth ingot and then cast by suction.

[0091] (4) After the alloy button ingot has completely cooled, open the furnace door and take out the sample.

[0092] Example 3

[0093] This embodiment provides a high-performance rare-earth high-manganese steel material with negative enthalpy of mixing, comprising the following molar percentage components: Fe 56.73%, Mn 18%, Al 11%, Cr 8%, Mo 0.25%, Ce 0.02%, Si 2%, and C 4%, which can be denoted as Fe 56.73 Mn 18 Al 11 Cr8Mo 0.25 Ce 0.02 Si2C4 has a mixing enthalpy of -15.23 kJ / mol.

[0094] The preparation method of the negative enthalpy high-manganese stainless steel material includes the following steps:

[0095] (1) Place the high-purity raw material particles of Fe, Mn, Al, Cr, Mo, Ce, Si and C (all with a purity greater than 99.9%) in an ultrasonic cleaner and clean them twice. Then, according to the molar percentage of each component in Example 3, weigh the high-purity raw material particles of Fe, Mn, Al, Cr, Mo, Ce, Si and C and place them in a water-cooled metal crucible in order of melting point from low to high. Place the raw material particles with the lowest melting point on the top layer and the raw material particles with the highest melting point on the surface layer. Place sponge titanium in the middle copper mold.

[0096] (2) Close the furnace door of the electric arc melting furnace, turn on the circulating water, turn on the mechanical pump, and perform vacuuming. When the vacuum degree is less than 5 Pa, turn on the molecular pump to further vacuum. When the vacuum degree reaches 7.0 × 10 Pa... -4 At Pa, 99.99% pure argon gas (as a protective gas) is introduced to 0.05 MPa, and sponge titanium is arc-melted twice in a high-purity argon atmosphere to absorb residual oxygen;

[0097] (3) Use a large current to perform arc ignition melting of the raw materials (melting voltage 12 V, melting current 430 A, melting time 2 min) to melt and mix all the metal particles evenly. After the alloy button is cast and cooled, it is flipped by a robot and the same method (melting voltage 12 V, melting current 430 A, melting time 2 min) is used for the second, third, fourth and fifth arc ignition melting. Magnetic stirring is turned on during each melting process after the second melting. After each melting, the alloy button needs to be flipped 180 degrees. A total of 5 meltings are performed to make the alloy composition more uniform. Magnetic stirring is turned off during the last melting to make it a smooth ingot and then cast by suction.

[0098] (4) After the alloy button ingot has completely cooled, open the furnace door and take out the sample.

[0099] Example 4

[0100] This embodiment provides a high-performance rare-earth high-manganese steel material with negative enthalpy of mixing, comprising the following molar percentage components: Fe 55.98%, Mn 18%, Al 11%, Cr 8%, Mo 1%, Gd 0.02%, Si 2%, and C 4%, which can be denoted as Fe 55.98 Mn18Al 11 Cr8Mo1Gd 0.02 Si2C4 has a mixing enthalpy of -14.94 kJ / mol.

[0101] The preparation method of the negative enthalpy high-manganese stainless steel material includes the following steps:

[0102] (1) Place the high-purity raw material particles of Fe, Mn, Al, Cr, Mo, Gd, Si and C (all with a purity greater than 99.9%) in an ultrasonic cleaner and clean them twice. Then, according to the molar percentage of each component in Example 4, weigh the high-purity raw material particles of Fe, Mn, Al, Cr, Mo, Gd, Si and C and place them in a water-cooled metal crucible in order of melting point from low to high. Place the raw material particles with the lowest melting point on the top layer and the raw material particles with the highest melting point on the surface layer. Place sponge titanium in the middle copper mold.

[0103] (2) Close the furnace door of the electric arc melting furnace, turn on the circulating water, turn on the mechanical pump, and perform vacuuming. When the vacuum degree is less than 5 Pa, turn on the molecular pump to further vacuum. When the vacuum degree reaches 7.0 × 10 Pa... -4 At Pa, 99.99% pure argon gas (as a protective gas) is introduced to 0.05 MPa, and sponge titanium is arc-melted twice in a high-purity argon atmosphere to absorb residual oxygen;

[0104] (3) Use a large current to perform arc ignition melting of the raw materials (melting voltage 12 V, melting current 380 A, melting time 2 min) to melt and mix all the metal particles evenly. After the alloy button is cast and cooled, it is flipped by a robot and the same method (melting voltage 12 V, melting current 380 A, melting time 2 min) is used to perform the second, third, fourth and fifth arc ignition melting. Magnetic stirring is turned on during each melting process after the second one. After each melting, the alloy button needs to be flipped 180 degrees. A total of 5 meltings are performed to make the alloy composition more uniform. Magnetic stirring is turned off during the last melting to make it into a smooth ingot and then cast by suction.

[0105] (4) After the alloy button ingot has completely cooled, open the furnace door and take out the sample.

[0106] Example 5

[0107] This embodiment provides a high-performance rare-earth high-manganese steel material with negative enthalpy of mixing, comprising the following molar percentage components: Fe 55.96%, Mn 18%, Al 11%, Cr 8%, Mo 1%, Gd 0.04%, Si 2%, and C 4%, which can be denoted as Fe 55.96 Mn18Al 11 Cr8Mo1Gd 0.04 Si2C4 has a mixing enthalpy of -14.95 kJ / mol.

[0108] The preparation method of the negative enthalpy high-manganese stainless steel material includes the following steps:

[0109] (1) Place the high-purity raw material particles of Fe, Mn, Al, Cr, Mo, Gd, Si and C (all with a purity greater than 99.9%) in an ultrasonic cleaner and clean them twice. Then, according to the molar percentage of each component in Example 5, weigh the high-purity raw material particles of Fe, Mn, Al, Cr, Mo, Gd, Si and C and place them in a water-cooled metal crucible in order of melting point from low to high. Place the raw material particles with the lowest melting point on the top layer and the raw material particles with the highest melting point on the surface layer. Place sponge titanium in the middle copper mold.

[0110] (2) Close the furnace door of the electric arc melting furnace, turn on the circulating water, turn on the mechanical pump, and perform vacuuming. When the vacuum degree is less than 5 Pa, turn on the molecular pump to further vacuum. When the vacuum degree reaches 7.0 × 10 Pa... -4 At Pa, 99.99% pure argon gas (as a protective gas) is introduced to 0.05 MPa, and sponge titanium is arc-melted twice in a high-purity argon atmosphere to absorb residual oxygen;

[0111] (3) Use a large current to perform arc ignition melting of the raw materials (melting voltage 12 V, melting current 400 A, melting time 2 min) to melt and mix all the metal particles evenly. After the alloy button is cast and cooled, it is flipped by a robot and the same method (melting voltage 12 V, melting current 400 A, melting time 2 min) is used to perform the second, third, fourth and fifth arc ignition melting. Magnetic stirring is turned on during each melting process after the second melting. After each melting, the alloy button needs to be flipped 180 degrees. A total of 5 meltings are performed to make the alloy composition more uniform. Magnetic stirring is turned off during the last melting to make it into a smooth ingot and then cast by suction.

[0112] (4) After the alloy button ingot has completely cooled, open the furnace door and take out the sample.

[0113] Example 6

[0114] This embodiment provides a high-performance rare-earth high-manganese steel material with negative enthalpy of mixing, comprising the following molar percentage components: Fe 55.92%, Mn 18%, Al 11%, Cr 8%, Mo 1%, Gd 0.08%, Si 2%, and C 4%, which can be denoted as Fe 55.92 Mn18Al 11 Cr8Mo1Gd 0.08 Si2C4 has a mixing enthalpy of -14.97 kJ / mol.

[0115] The preparation method of the negative enthalpy high-manganese stainless steel material includes the following steps:

[0116] (1) Place the high-purity raw material particles of Fe, Mn, Al, Cr, Mo, Gd, Si and C (all with a purity greater than 99.9%) in an ultrasonic cleaner and clean them twice. Then, according to the molar percentage of each component in Example 6, weigh the high-purity raw material particles of Fe, Mn, Al, Cr, Mo, Gd, Si and C and place them in a water-cooled metal crucible in order of melting point from low to high. Place the raw material particles with the lowest melting point on the top layer and the raw material particles with the highest melting point on the surface layer. Place sponge titanium in the middle copper mold.

[0117] (2) Close the furnace door of the electric arc melting furnace, turn on the circulating water, turn on the mechanical pump, and perform vacuuming. When the vacuum degree is less than 5 Pa, turn on the molecular pump to further vacuum. When the vacuum degree reaches 7.0 × 10 Pa... -4 At Pa, 99.99% pure argon gas (as a protective gas) is introduced to 0.05 MPa, and sponge titanium is arc-melted twice in a high-purity argon atmosphere to absorb residual oxygen;

[0118] (3) Use a large current to perform arc ignition melting of the raw materials (melting voltage 12 V, melting current 420 A, melting time 2 min) to melt and mix all the metal particles evenly. After the alloy button is cast and cooled, it is flipped by a robot and the same method (melting voltage 12 V, melting current 420 A, melting time 2 min) is used to perform the second, third, fourth and fifth arc ignition melting. Magnetic stirring is turned on during each melting process after the second melting. After each melting, the alloy button needs to be flipped 180 degrees. A total of 5 meltings are performed to make the alloy composition more uniform. Magnetic stirring is turned off during the last melting to make it a smooth ingot and then cast by suction.

[0119] (4) After the alloy button ingot has completely cooled, open the furnace door and take out the sample.

[0120] Example 7

[0121] This embodiment provides a high-performance rare-earth high-manganese steel material with negative enthalpy of mixing, comprising the following molar percentage components: Fe 59.22%, Mn 18%, Al 9%, Cr 8%, Mo 0.7%, Ce 0.08%, Si 2%, and C 3%, which can be denoted as Fe 59.22 Mn 18 Al9Cr8Mo 0.7 Ce 0.08 Si2C3 has a mixing enthalpy of -12.52 kJ / mol.

[0122] The preparation method of the negative enthalpy high-manganese stainless steel material includes the following steps:

[0123] (1) Place the high-purity raw material particles of Fe, Mn, Al, Cr, Mo, Ce, Si and C (all with a purity greater than 99.9%) in an ultrasonic cleaner and clean them twice. Then, according to the molar percentage of each component in Example 7, weigh the high-purity raw material particles of Fe, Mn, Al, Cr, Mo, Ce, Si and C and place them in a water-cooled metal crucible in order of melting point from low to high. Place the raw material particles with the lowest melting point on the top layer and the raw material particles with the highest melting point on the surface layer. Place sponge titanium in the middle copper mold.

[0124] (2) Close the furnace door of the electric arc melting furnace, turn on the circulating water, turn on the mechanical pump, and perform vacuuming. When the vacuum degree is less than 5 Pa, turn on the molecular pump to further vacuum. When the vacuum degree reaches 7.0 × 10 Pa... -4 At Pa, 99.99% pure argon gas (as a protective gas) is introduced to 0.05 MPa, and sponge titanium is arc-melted twice in a high-purity argon atmosphere to absorb residual oxygen;

[0125] (3) Use a large current to perform arc ignition melting of the raw materials (melting voltage 12 V, melting current 420 A, melting time 2 min) to melt and mix all the metal particles evenly. After the alloy button is cast and cooled, it is flipped by a robot and the same method (melting voltage 12 V, melting current 420 A, melting time 2 min) is used to perform the second, third, fourth and fifth arc ignition melting. Magnetic stirring is turned on during each melting process after the second melting. After each melting, the alloy button needs to be flipped 180 degrees. A total of 5 meltings are performed to make the alloy composition more uniform. Magnetic stirring is turned off during the last melting to make it a smooth ingot and then cast by suction.

[0126] (4) After the alloy button ingot has completely cooled, open the furnace door and take out the sample.

[0127] Example 8

[0128] This embodiment provides a high-performance rare-earth high-manganese steel material with negative enthalpy of mixing, comprising the following molar percentage components: Fe 59.18%, Mn 18%, Al 9%, Cr 8%, Mo 0.7%, Ce 0.08%, Pb 0.04%, Si 2%, and C 3%, which can be denoted as Fe 59.18 Mn 18 Al9Cr8Mo 0.7 Ce 0.08 Pb 0.04 Si2C3 has a mixing enthalpy of -12.46 kJ / mol.

[0129] The preparation method of the negative enthalpy high-manganese stainless steel material includes the following steps:

[0130] (1) Place the high-purity raw material particles of Fe, Mn, Al, Cr, Mo, Ce, Pb, Si and C (all with a purity greater than 99.9%) in an ultrasonic cleaner and clean them twice. Then, according to the molar percentage of each component in Example 8, weigh the high-purity raw material particles of Fe, Mn, Al, Cr, Mo, Ce, Pb, Si and C and place them in a water-cooled metal crucible in order of melting point from low to high. Place the raw material particles with the lowest melting point on the top layer and the raw material particles with the highest melting point on the surface layer. Place sponge titanium in the middle copper mold.

[0131] (2) Close the furnace door of the electric arc melting furnace, turn on the circulating water, turn on the mechanical pump, and perform vacuuming. When the vacuum degree is less than 5 Pa, turn on the molecular pump to further vacuum. When the vacuum degree reaches 7.0 × 10 Pa... -4 At Pa, 99.99% pure argon gas (as a protective gas) is introduced to 0.05 MPa, and sponge titanium is arc-melted twice in a high-purity argon atmosphere to absorb residual oxygen;

[0132] (3) Use a large current to perform arc ignition melting of the raw materials (melting voltage 12 V, melting current 435 A, melting time 2 min) to melt and mix all the metal particles evenly. After the alloy button is cast and cooled, it is flipped by a robot and the same method (melting voltage 12 V, melting current 435 A, melting time 2 min) is used to perform the second, third, fourth, fifth and sixth arc ignition melting. Magnetic stirring is turned on during each melting process after the second one. After each melting, the alloy button needs to be flipped 180 degrees. A total of 6 meltings are performed to make the alloy composition more uniform. Magnetic stirring is turned off during the last melting to make it a smooth ingot and then cast by suction.

[0133] (4) After the alloy button ingot has completely cooled, open the furnace door and take out the sample.

[0134] Example 9

[0135] This embodiment provides a high-performance rare-earth high-manganese steel material with negative enthalpy of mixing, comprising the following molar percentage components: Fe 59.68%, Mn 18%, Al 9%, Cr 8%, Mo 0.7%, Ce 0.08%, Pb 0.04%, Si 1.5%, and C 3%, which can be denoted as Fe 59.68 Mn 18 Al9Cr8Mo 0.7 Ce 0.08 Pb 0.04 Si 1.5 C3 has a mixing enthalpy of -11.87 kJ / mol.

[0136] The preparation method of the negative enthalpy high-manganese stainless steel material includes the following steps:

[0137] (1) Place the high-purity raw material particles of Fe, Mn, Al, Cr, Mo, Ce, Pb, Si and C (all with a purity greater than 99.9%) in an ultrasonic cleaner and clean them twice. Then, according to the molar percentage of each component in Example 9, weigh the high-purity raw material particles of Fe, Mn, Al, Cr, Mo, Ce, Pb, Si and C and place them in a water-cooled metal crucible in order of melting point from low to high. Place the raw material particles with the lowest melting point on the top layer and the raw material particles with the highest melting point on the surface layer. Place sponge titanium in the middle copper mold.

[0138] (2) Close the furnace door of the electric arc melting furnace, turn on the circulating water, turn on the mechanical pump, and perform vacuuming. When the vacuum degree is less than 5 Pa, turn on the molecular pump to further vacuum. When the vacuum degree reaches 7.0 × 10 Pa... -4At Pa, 99.99% pure argon gas (as a protective gas) is introduced to 0.05 MPa, and sponge titanium is arc-melted twice in a high-purity argon atmosphere to absorb residual oxygen;

[0139] (3) Use a large current to perform arc ignition melting of the raw materials (melting voltage 12 V, melting current 445 A, melting time 2 min) to melt and mix all the metal particles evenly. After the alloy button is cast and cooled, it is flipped by a robot and the same method (melting voltage 12 V, melting current 445 A, melting time 2 min) is used for the second, third, fourth, fifth and sixth arc ignition melting. Magnetic stirring is turned on during each melting process after the second melting. After each melting, the alloy button needs to be flipped 180 degrees. A total of 6 meltings are performed to make the alloy composition more uniform. Magnetic stirring is turned off during the last melting to make it a smooth ingot and then cast by suction.

[0140] (4) After the alloy button ingot has completely cooled, open the furnace door and take out the sample.

[0141] Comparative Example 1

[0142] This comparative example provides a rare earth high-manganese steel material comprising the following molar percentages: Fe 56.50%, Mn 18%, Al 11%, Cr 8%, Mo 0.50%, Si 2%, and C 4%, which can be denoted as Fe 56.50 Mn 18 Al 11 Cr8Mo 0.50 Si2C4 has a mixing enthalpy of -12.50 kJ / mol.

[0143] The preparation method of the rare earth high-manganese steel material includes the following steps:

[0144] (1) Place the high-purity raw material particles of Fe, Mn, Al, Cr, Mo, Si and C (all with a purity greater than 99.9%) in an ultrasonic cleaner and clean them twice. Then, according to the molar percentage of each component in Comparative Example 1, weigh the high-purity raw material particles of Fe, Mn, Al, Cr, Mo, Si and C and place them in a water-cooled metal crucible in order of melting point from low to high. Place the raw material particles with the lowest melting point on the top layer and the raw material particles with the highest melting point on the surface layer. Place the sponge titanium in the middle copper mold.

[0145] (2) Close the furnace door of the electric arc melting furnace, turn on the circulating water, turn on the mechanical pump, and perform vacuuming. When the vacuum degree is less than 5 Pa, turn on the molecular pump to further vacuum. When the vacuum degree reaches 7.0 × 10 Pa... -4At Pa, 99.99% pure argon gas (as a protective gas) is introduced to 0.05 MPa, and sponge titanium is arc-melted twice in a high-purity argon atmosphere to absorb residual oxygen;

[0146] (3) Use a large current to perform arc ignition melting of the raw materials (melting voltage 12 V, melting current 400 A, melting time 2 min) to melt and mix all the metal particles evenly. After the alloy button is cast and cooled, it is flipped by a robot and the same method (melting voltage 12 V, melting current 400 A, melting time 2 min) is used to perform the second, third, fourth and fifth arc ignition melting. Magnetic stirring is turned on during each melting process after the second melting. After each melting, the alloy button needs to be flipped 180 degrees. A total of 5 meltings are performed to make the alloy composition more uniform. Magnetic stirring is turned off during the last melting to make it into a smooth ingot and then cast by suction.

[0147] (4) After the alloy button ingot has completely cooled, open the furnace door and take out the sample.

[0148] Comparative Example 2

[0149] This comparative example provides a rare earth high-manganese steel material, comprising the following molar percentage components: Fe 59.26%, Mn 18%, Al 9%, Cr 8%, Mo 0.7%, Pb 0.04%, Si 2%, and C 3%, which can be denoted as Fe 59.26 Mn 18 Al9Cr8Mo 0.7 Pb 0.0 4Si2C3 has a mixing enthalpy of -12.47 kJ / mol.

[0150] The preparation method of the rare earth high-manganese steel material includes the following steps:

[0151] (1) Place the high-purity raw material particles of Fe, Mn, Al, Cr, Mo, Pb, Si and C (all with a purity greater than 99.9%) in an ultrasonic cleaner and clean them twice. Then, according to the molar percentage of each component in Comparative Example 2, weigh the high-purity raw material particles of Fe, Mn, Al, Cr, Mo, Pb, Si and C and place them in a water-cooled metal crucible in order of melting point from low to high. Place the raw material particles with the lowest melting point on the top layer and the raw material particles with the highest melting point on the surface layer. Place sponge titanium in the middle copper mold.

[0152] (2) Close the furnace door of the electric arc melting furnace, turn on the circulating water, turn on the mechanical pump, and perform vacuuming. When the vacuum degree is less than 5 Pa, turn on the molecular pump to further vacuum. When the vacuum degree reaches 7.0 × 10⁻⁶ Pa, perform vacuuming. -4At Pa, 99.99% pure argon gas (as a protective gas) is introduced to 0.05 MPa, and sponge titanium is arc-melted twice in a high-purity argon atmosphere to absorb residual oxygen;

[0153] (3) Use a large current to perform arc ignition melting of the raw materials (melting voltage 12 V, melting current 420 A, melting time 2 min) to melt and mix all the metal particles evenly. After the alloy button is cast and cooled, it is flipped by a robot and the same method (melting voltage 12 V, melting current 420 A, melting time 2 min) is used to perform the second, third, fourth and fifth arc ignition melting. Magnetic stirring is turned on during each melting process after the second melting. After each melting, the alloy button needs to be flipped 180 degrees. A total of 5 meltings are performed to make the alloy composition more uniform. Magnetic stirring is turned off during the last melting to make it a smooth ingot and then cast by suction.

[0154] (4) After the alloy button ingot has completely cooled, open the furnace door and take out the sample.

[0155] test:

[0156] The Fe prepared in Examples 1-9 a Mn b Al c Cr d Mo e Pb f RE g Si h C i X-ray diffraction (XRD) tests were performed on a series of high-performance rare-earth high-manganese steel materials with negative enthalpy of mixing and the high-manganese steel materials prepared in Comparative Examples 1-2. The results are as follows: Figure 1 As shown; from Figure 1 As can be seen from the examples 1-9, the Fe prepared in these examples... a Mn b Al c Cr d Mo e Pb f RE g Si h C i The series of high-performance rare earth high-manganese steel materials with negative mixing enthalpy and the high-manganese steel materials prepared in Comparative Examples 1-2 all contain face-centered cubic (FCC) structures.

[0157] Based on Archimedes' principle, the Fe prepared in Examples 1-9 was measured respectively. a Mn b Al c Cr d Mo e Pb f REg Si h C i The masses of the high-performance rare-earth high-manganese steel materials with negative enthalpy of mixing and the high-manganese steel materials prepared in Comparative Examples 1-2 in air and immersed in the test fluid were substituted into the corresponding formulas to calculate the density of each sample; the results show that Fe 55.92 Mn 18 Al 11 Cr8Mo1Ce 0.08 The density of Si2C4 is 6.68 g / cm³. 3 Fe 56.48 Mn 18 Al 11 Cr8Mo 0.50 Ce 0.02 The density of Si2C4 is 6.67 g / cm³. 3 Fe 56.73 Mn 18 Al 11 Cr8Mo 0.25 Ce 0.02 The density of Si2C4 is 6.66 g / cm³. 3 Fe 55.98 Mn 18 Al 11 Cr8Mo1Gd 0.02 The density of Si2C4 is 6.67 g / cm³. 3 Fe 55.96 Mn 18 Al 11 Cr8Mo1Gd 0.04 The density of Si2C4 is 6.68 g / cm³. 3 Fe 55.92 Mn 18 Al 11 Cr8Mo1Gd 0.08 The density of Si2C4 is 6.68 g / cm³. 3 Fe 59.22 Mn 18 Al9Cr8Mo 0.7 Ce 0.08 The density of Si2C3 is 6.82 g / cm³. 3 Fe 59.18 Mn 18 Al9Cr8Mo 0.7 Ce 0.08 Pb 0.04 The density of Si2C3 is 6.84 g / cm³. 3 Fe 59.68 Mn 18 Al9Cr8Mo 0.7 Ce 0.08 Pb0.04 Si 1.5 The density of C3 is 6.88 g / cm³. 3 Fe 56.50 Mn 18 Al 11 Cr8Mo 0.50 The density of Si2C4 is 6.67 g / cm³. 3 Fe 59.26 Mn 18 Al9Cr8Mo 0.7 Pb 0.04 The density of Si2C3 is 6.84 g / cm³. 3 .

[0158] The Fe prepared in Examples 1-9 were processed using wire electrical discharge machining. a Mn b Al c Cr d Mo e Pb f RE g Si h C i Dog-bone shaped tensile specimens with gauge lengths of 15 mm, widths of 2.5 mm, and thicknesses of 1.0 mm were cut from a series of high-performance rare-earth high-manganese steel materials with negative enthalpy of mixing and the high-manganese steel materials prepared in Comparative Examples 1-2. These specimens were then tested on an EXCEED Model E43 universal testing machine at a constant strain rate of 5 × 10⁻⁶. -4 s -1 Tensile tests were performed, and tensile strain was monitored using an extensometer. The results are as follows: Figure 2 As shown; from Figure 2 As can be seen from the examples 1-9, the Fe prepared in these examples... a Mn b Al c Cr d Mo e Pb f RE g Si h C i The series of high-performance rare-earth high-manganese steel materials with negative mixing enthalpy and the high-manganese steel materials prepared in Comparative Examples 1-2 both possess high strength and high plasticity in terms of mechanical properties, among which: Fe 55.92 Mn 18 Al 11 Cr8Mo1Ce 0.08 The room temperature tensile yield strength of Si2C4 is 483 MPa, the breaking strength is 890 MPa, and the uniform elongation is 45.0%; Fe 56.48 Mn 18 Al 11 Cr8Mo 0.50Ce 0.02 The room temperature tensile yield strength of Si2C4 is 357 MPa, the breaking strength is 758 MPa, and the uniform elongation is 63.1%; Fe 56.7 3Mn 18 Al 11 Cr8Mo 0.25 Ce 0.02 The room temperature tensile yield strength of Si₂C₄ is 380 MPa, the breaking strength is 830 MPa, and the uniform elongation is 68.1%; Fe 55.98 Mn 18 Al 11 Cr8Mo1Gd 0.02 The room temperature tensile yield strength of Si₂C₄ is 400 MPa, the breaking strength is 847 MPa, and the uniform elongation is 63.1%; Fe 55.96 Mn 18 Al 11 Cr8Mo1Gd 0.04 The room temperature tensile yield strength of Si2C4 is 407 MPa, the breaking strength is 857 MPa, and the uniform elongation is 55.9%; Fe 55.92 Mn 18 Al 11 Cr8Mo1Gd 0.08 The room temperature tensile yield strength of Si2C4 is 395 MPa, the breaking strength is 644 MPa, and the uniform elongation is 22.3%; Fe 59.22 Mn 18 Al9Cr8Mo 0.7 Ce 0.08 The room temperature tensile yield strength of Si2C3 is 477 MPa, the breaking strength is 920 MPa, and the uniform elongation is 42.3%; Fe 59.18 Mn 18 Al9Cr8Mo 0.7 Ce 0.08 Pb 0.04 The room temperature tensile yield strength of Si2C3 is 509 MPa, the breaking strength is 963 MPa, and the uniform elongation is 44.6%; Fe 59.68 Mn 18 Al9Cr8Mo 0.7 Ce 0.08 Pb 0.04 Si 1.5 C3 has a room temperature tensile yield strength of 460 MPa, a breaking strength of 910 MPa, and a uniform elongation of 48.2%; Fe 56.50 Mn 18 Al 11 Cr8Mo 0.50The room temperature tensile yield strength of Si2C4 is 410 MPa, the breaking strength is 710 MPa, and the uniform elongation is 35.4%; Fe 59.26 Mn 18 Al9Cr8Mo 0.7 Pb 0.04 The room temperature tensile yield strength of Si2C3 is 480 MPa, the breaking strength is 789 MPa, and the uniform elongation is 24.2%.

[0159] Corrosion resistance test: Using a CS 235M potentiostat, the Fe prepared in Examples 1-9 were tested respectively. a Mn b Al c Cr d Mo e Pb f RE g Si h C i The pitting corrosion resistance of a series of high-performance rare-earth high-manganese steel materials with negative enthalpy of mixing and the high-manganese steel material samples prepared in Comparative Examples 1-2 in 0.6 mol / L NaCl aqueous solution (25±1 ℃) was investigated. Specifically, a three-electrode electrolytic cell was used: a saturated calomel reference electrode, a platinum sheet counter electrode, and a working electrode for the high-manganese steel material sample. The working electrode sample size was 12.5×8×1 mm. 3 After the copper wire is connected, it is sealed with epoxy resin by cold mounting; the potentiodynamic polarization test starts from -0.5 V of the corrosion potential Ecorr and scans towards the anode at a rate of 0.167 mV / s until the pitting potential signal appears.

[0160] The corrosion resistance test results are as follows: Figure 3-6 As shown; from Figure 3-6 As can be seen from the examples 1-9, the Fe prepared in these examples... a Mn b Al c Cr d Mo e Pb f RE g Si h C i The series of high-performance rare-earth high-manganese steel materials with negative enthalpy of mixing exhibit good corrosion resistance, while the high-manganese steel materials prepared in Comparative Examples 1-2 show significantly poorer corrosion resistance; specifically: the Fe prepared in Examples 1-9 a Mn b Al c Cr d Mo e Pb f RE g Si h C iA series of high-performance rare-earth high-manganese steel materials with negative mixing enthalpy, Fe 55.92 Mn 18 Al 11 Cr8Mo1Ce 0.08 The corrosion potential of Si2C4 is -0.17V, and the pitting potential is 0.10V; Fe 56.48 Mn 18 Al 11 Cr8Mo 0.50 Ce 0.02 The corrosion potential of Si2C4 is -0.26V, and the pitting potential is -0.07V; Fe 56.73 Mn 18 Al 11 Cr8Mo 0.25 Ce 0.02 The corrosion potential of Si2C4 is -0.21V, and the pitting potential is -0.04V; Fe 55.98 Mn 18 Al 11 Cr8Mo1Gd 0.02 The corrosion potential of Si2C4 is -0.19V, and the pitting potential is 0.15V; Fe 55.96 Mn 18 Al 11 Cr8Mo1Gd 0.04 The corrosion potential of Si2C4 is -0.18V, and the pitting potential is 0.08V; Fe 55.92 Mn 18 Al 11 Cr8Mo1Gd 0.08 The corrosion potential of Si2C4 is -0.16V, and the pitting potential is -0.01V; Fe 59.22 Mn 18 Al9Cr8Mo 0.7 Ce 0.08 The corrosion potential of Si2C3 is -0.24V, and the pitting potential is 0.01V; Fe 59.18 Mn 18 Al9Cr8Mo 0.7 Ce 0.08 Pb 0.04 The corrosion potential of Si2C3 is -0.17V, and the pitting potential is -0.04V; Fe 59.68 Mn 18 Al9Cr8Mo 0.7 Ce 0.08 Pb 0.04 Si 1.5 The C3 corrosion potential is -0.19V, and the pitting potential is -0.08V; that is, the Fe prepared in Examples 1-9 a Mn b Al c Crd Mo e Pb f RE g Si h C i All high-performance rare-earth high-manganese steel materials with negative enthalpy of mixing exhibit passivation behavior and pitting potentials greater than -0.10V; while in the high-manganese steel materials prepared in Comparative Examples 1-2, Fe... 56.50 Mn 18 Al 11 Cr8Mo 0.50 The corrosion potential of Si2C4 is -0.27V (no passivation behavior); Fe 59.26 Mn 18 Al9Cr8Mo 0.7 Pb 0.04 The corrosion potential of Si2C3 is -0.29V (no passivation behavior).

[0161] Comparative analysis of the corrosion resistance test results of Comparative Example 1 and Examples 1-6 shows that reducing the Mo content will decrease the pitting potential of the alloy and weaken its pitting resistance. Rare earth elements Ce and Gd will significantly increase the pitting potential, but excessive addition of rare earth elements will cause a decrease in toughness and pitting potential, which is not conducive to improving the corrosion resistance of the alloy. From the corrosion resistance test results of Comparative Example 2 and Examples 7-9, it can be found that Example 7, which did not add Pb, has the best corrosion resistance. This is because lead-rich single or composite inclusions are easily precipitated at the grain boundaries during the cooling process. These inclusions will preferentially dissolve in the corrosive environment, providing pitting nucleation sites and thus deteriorating the corrosion resistance.

[0162] The above embodiments are merely examples of several implementation methods of the present invention, and their descriptions are relatively specific and detailed, but they should not be construed as limiting the scope of the invention patent.

[0163] It should be noted that those skilled in the art can make various modifications and improvements without departing from the inventive concept, and these all fall within the scope of protection of this invention. Therefore, the scope of protection of this patent should be determined by the appended claims.

Claims

1. A high-performance rare-earth high-manganese steel material with negative mixing enthalpy, characterized in that, The rare earth high-manganese steel material is Fe. a Mn b Al c Cr d Mo e Pb f RE g Si h C i ; in: RE is either Ce or Gd; a, b, c, d, e, f, g, h, and i correspond to the molar percentages of each element, with 16% ≤ b ≤ 20%, 8% ≤ c ≤ 12%, 7% ≤ d ≤ 9%, 0 < e ≤ 1.8%, 0 ≤ f ≤ 0.1%, 0 < g ≤ 0.1%, 1% ≤ h ≤ 3%, and 2% ≤ i ≤ 5%, with the balance being Fe and unavoidable impurities. The rare earth high manganese steel material has a face-centered cubic structure.

2. The high-performance rare-earth high-manganese steel material with negative mixing enthalpy according to claim 1, characterized in that, The rare earth high manganese steel material has a purity of ≥99.8% for the corresponding raw materials of iron, manganese, aluminum, chromium, molybdenum, lead, cerium, gadolinium, silicon and carbon.

3. The high-performance rare-earth high-manganese steel material with negative mixing enthalpy according to claim 1, characterized in that, In the rare earth high manganese steel material The enthalpy of mixing between cerium and gadolinium with iron and manganese are both between -1 and 3 kJ / mol. The enthalpy of mixing between cerium and gadolinium with chromium and molybdenum are both between 10 and 30 kJ / mol. The enthalpy of mixing cerium and gadolinium with aluminum, lead, silicon and carbon are all between -120 and -30 kJ / mol. The enthalpy of mixing lead with iron, manganese, aluminum, chromium and molybdenum is between 10 and 50 kJ / mol.

4. The high-performance rare-earth high-manganese steel material with negative enthalpy of mixing according to any one of claims 1-3, characterized in that, The rare earth high-manganese steel material is Fe. 55.92 Mn 18 Al 11 Cr8Mo1Ce 0.08 Si2C4, Fe 56.48 Mn 18 Al 11 Cr8Mo 0.50 Ce 0.02 Si2C4, Fe 56.73 Mn 18 Al 11 Cr8Mo 0.25 Ce 0.02 Si2C4, Fe 55.98 Mn 18 Al 11 Cr8Mo1Gd 0.02 Si2C4, Fe 55.96 Mn 18 Al 11 Cr8Mo1Gd 0.04 Si2C4, Fe 55.92 Mn 18 Al 11 Cr8Mo1Gd 0.08 Si2C4, Fe 59.22 Mn 18 Al9Cr8Mo 0.7 Ce 0.08 Si2C3, Fe 59.18 Mn18Al9Cr8Mo 0.7 Ce 0.08 Pb 0.04 Si2C3, Fe 59.68 Mn 18 Al9Cr8Mo 0.7 Ce 0.08 Pb 0.04 Si 1.5 One of C3.

5. The high-performance rare-earth high-manganese steel material with negative mixing enthalpy according to claim 4, characterized in that, The mixed enthalpy values ​​of the rare earth high manganese steel materials are all between -16 and -10 kJ / mol.

6. A method for preparing a high-performance rare-earth high-manganese steel material with negative enthalpy of mixing as described in any one of claims 1-5, characterized in that, The rare earth high-manganese steel material is Fe. a Mn b Al c Cr d Mo e Pb f RE g Si h C i ; Where: RE is Ce or Gd; a, b, c, d, e, f, g, h, and i correspond to the molar percentages of each element, with 16% ≤ b ≤ 20%, 8% ≤ c ≤ 12%, 7% ≤ d ≤ 9%, 0 < e ≤ 1.8%, 0 ≤ f ≤ 0.1%, 0 < g ≤ 0.1%, 1% ≤ h ≤ 3%, and 2% ≤ i ≤ 5%, with the balance being Fe and unavoidable impurities. The rare earth high manganese steel material has a face-centered cubic structure. The preparation method of the rare earth high-manganese steel material includes the following steps: According to the composition and molar percentage of the rare earth high manganese steel material, calculate and weigh each metal raw material, and put each metal raw material into the water-cooled metal crucible in order of melting point from low to high. The metal raw material with the lowest melting point is placed at the bottom and the metal raw material with the highest melting point is placed on the surface. Sponge titanium is placed in the middle copper mold. Arc melting is carried out in an oxygen-free environment until it is fully mixed to obtain the rare earth high manganese steel material.

7. The method for preparing high-performance rare-earth high-manganese steel material with negative enthalpy of mixing according to claim 6, characterized in that, The anaerobic environment is achieved through the following process: A mechanical pump was used to evacuate the vacuum to a level less than 5 Pa, followed by a molecular pump to evacuate the vacuum to a level less than 7 × 10⁻⁶ Pa. -4 Pa, then 99.99% pure argon gas is introduced to 0.05 MPa, and finally the sponge titanium is melted twice by arc ignition to absorb residual oxygen.

8. The method for preparing high-performance rare-earth high-manganese steel material with negative enthalpy of mixing according to claim 6, characterized in that, The number of times the metal raw material is ignited and melted is greater than 4. After each ignition and melting, the alloy in the crucible is turned over before the next ignition and melting. Before the next ignition and melting of the alloy, the sponge titanium is melted and oxygen absorbed twice.

9. The method for preparing high-performance rare-earth high-manganese steel material with negative enthalpy of mixing according to claim 8, characterized in that, The melting time for each arc-ignition melting is 1.0-2.0 min, and in addition to the first and last arc-ignition melting, the arc-ignition melting of the metal raw materials also includes magnetic stirring of the melt.

10. The method for preparing high-performance rare-earth high-manganese steel material with negative enthalpy of mixing according to claim 8 or 9, characterized in that, The melting voltage and melting current for the arc-ignition melting are 10-15 V and 320-450 A, respectively.